Comparative analysis of traditional and new approach to urban management in Iran - Redzuan, Ma’rof; Kiani, Akbar; Sardri, Farzali Salari; Edalati, Ali; Abbasi, Zhila (PSCI Publications, 2013)
Today, management are known as main factor and determinant of success for any organization and organizational, and aim to investment policy and performing programs. Cities also as a system and complex social discipline requires a management organize (Urban Management) for determining and achieving goals and coordinating activities and different dimensions of urban sustainable development. Thus, the pattern of urban management shows cities management method in historical periods and different decision making fields and development of urban areas. In This article in spite of to understand and, of course developments in urban management levels in different periods, and expression present situation, its strengths and weaknesses are analyzing , and by using descriptive methods (Library Studies), secondary data analysis (documents) and content analysis techniques reviewing comparative analysis between traditional and new approach to urban management. In end, recommendations proposed for efficient building for urban management and development of decentralized urban management in Iran regard to challenges and modern management eye metric in cities (electronic and intelligent management, knowledge axis, and from within.